ROLE OF GAP JUNCTIONS AND CONNEXIN 43 IN CANCEROGENESIS AND TUMOR METASTASIS - Savić, Ivana (Medicinski podmladak, 2022)
Gap junctions are intercellular connections that enable direct communication between neighboring cells. They are important in tissue homeostasis, cell growth, and differentiation. They are composed of connexin proteins, of which the most common and most studied is connexin 43. The role of connexin 43 in the development and progression of tumors is contradictory. The aim of this paper is to summarize the current state of knowledge on the expression of connexin 43 in various primary and secondary tumors in order to explain its role in the development and progression of malignant tumors. Previous studies have examined the expression of connexin 43 in various primary and secondary tumors as well as its association with prognosis. The expression of connexin 43 has been shown to be associated with various aspects of tumor behavior. However, it has been shown that the expression of connexin 43 differs between different types and localizations of tumors, as well as between different stages in tumor progression, which indicates the complex role of connexin 43 in tumor evolution. Since gap junctions play a role in carcinogenesis, invasion, and metastasis of malignant cells, further studies should clarify whether connexin 43 can be used as a diagnostic biomarker.